An axis of Bernardo Santareno to the critical margin: "Confession" (1945) and memories of the Cuban story of the "A traição do Padre Martinho" (1969) - Moura, Susana (Revista Desassossego, 2020)
It has been assumed that Bernardo Santareno's dramatic work began with The Promise (1957). However, there are a number of previous works that have not been considered by critics and academia. Confession (1945) is one of those cases that I now refer to debate. The betrayal of Father Martinho (1969), due to the vicissitudes of censorship in Portugal, was performed by Rogério Paulo in Cuba. It was 1970 and this Portuguese director presents this play with the Cuban company Rita Montaner. Below, I present an overview of this case through three testimonies in the first person: two actors and a Cuban playwright who participated in this show. All of them were interviewed by me in the city of Havana in 2018.